Entrepreneurial personality, conscientiousness, self-control, and grit: The psychological side of self-employment - Postigo, Álvaro; Cuesta, Marcelino; García-Cueto, Eduardo (Anales de Psicología / Annals of Psychology, 2021)
The psychological approach to entrepreneurial activity helps to explain why people decide or not to undertake. The objective of this study is to analyze different entrepreneurial personality profiles, as well as to identify the personality variables that can explain becoming a self-employer. Using a sample of 586 participants (Mage = 39.31; SDage = 14.66), different entrepreneurial personality profiles were analyzed using latent profile analysis techniques. In addition, it was analyzed whether there were differences in other psychological variables based on the entrepreneurial personality profile. Finally, it was studied, using a structural equation model, if conscientiousness, self-control, grit and entrepreneurial personality help to explain why people become self-employed. The results support the existence of three latent profiles of entrepreneurial personality (low, medium and high), being high entrepreneurial personality the one profile that shows higher scores in other psychological variables, as well as a higher proportion of self-employers. The proposed structural equation model explains 2.6% of the variance of the variable being self-employed, so the personality variables help to explain a small part of entrepreneurial activity.